2006
DOI: 10.1577/t04-221.1
|View full text |Cite
|
Sign up to set email alerts
|

Admixture Analysis of Florida Largemouth Bass and Northern Largemouth Bass using Microsatellite Loci

Abstract: Microsatellite DNA variation was examined at 11 loci in five populations of Florida largemouth bass Micropterus salmoides floridanus (N ¼ 175) and eight populations of northern largemouth bass M. s. salmoides (N ¼ 249). Distinct allele frequencies with 33 private alleles between subspecies (threshold frequency, !0.05) and 19 private alleles among three geographic regions distinguished between Florida largemouth bass and northern largemouth bass as well as between northern largemouth bass from northern and sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 36 publications
2
41
0
2
Order By: Relevance
“…Genotyping was conducted based on a subset of microsatellite markers from Lutz‐Carrillo et al . () and Seyoum et al . ().…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…Genotyping was conducted based on a subset of microsatellite markers from Lutz‐Carrillo et al . () and Seyoum et al . ().…”
Section: Methodsmentioning
confidence: 84%
“…Subsets of each population were previously genotyped using diagnostic microsatellite markers (Lutz‐Carrillo et al . ; Seyoum et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The native Largemouth Bass had previously been identified as a unique lineage that was genetically divergent from other Largemouth Bass populations and exhibited glossohyal teeth, a morphological trait rarely observed in Largemouth Bass (Lutz‐Carrillo et al. ). Therefore, the diversity lost to introgression could not be recovered by reintroducing fish from any other drainage.…”
Section: Conservation Challengesmentioning
confidence: 99%
“…Note that the microsatellite admixture is calculated at the population level, while mtDNA admixture refers to the frequency of Lota l. lota (EB lineage) or L. l. maculosa (NA lineage) mtDNA in individuals in the population. Rhymer et al 2001;Fedorov et al 2003), though subspecies of closely related temperate fish are often found to interbreed freely at contact zones (reviewed in Utter 2001;Lutz-Carrillo et al 2006;Taylor et al 2007). In fact, interbreeding when no geographic barrier prevails is fundamental to the definition of fish subspecies (Nelson 1999;Haig et al 2006).…”
Section: Ecological Parapatry and Subspecies Differencesmentioning
confidence: 99%